Curcumin-loaded carrageenan nanoparticles: Fabrication, characterization, and assessment of the effects on osteoblasts mineralization - Nogueira, Lucas Fabrício Bahia; Cruz, Marcos Antônio Eufrásio; Tovani, Camila Bussola; Lopes, Helena Bacha; Beloti, Márcio Mateus; Ciancaglini, Pietro; Bottini, Massimo; Ramos, Ana Paula (Colloids and surfaces, B, Biointerfaces, 2022)
The use of Curcumin (CR) as a bioactive molecule to prevent and treat inflammation- related diseases is widespread. However, the high hydrophobicity hinders the in vivo bioavailability of CR, reducing its therapeutic index. In the present study, we described the use of nanoparticles (NPs) made of kappa-carrageenan (κ-Carr), a sulphated polysaccharide, as cost-effective, biodegradable and biocompatible CR carriers. CR-loaded κ-Carr nanoparticles (CR@Carr NPs) were prepared by mixing a κ-Carr aqueous solution with a CR ethanolic solution. The final suspension was centrifuged and re-suspended in phosphate buffer solution. The NPs' size was tuned by changing the concentration of the polysaccharide. CR@CarrNPs displayed high CR incorporation efficiency (~80 wt%) and a double-exponential curve of CR release at physiological conditions (37 °C and pH 7.4) with a cumulative drug release of 32 wt% after 24 h for the smaller NP. Our results also showed that CR@CarrNPs were not cytotoxic to osteoblasts at concentrations up to 1 μM. Confocal microscopy images revealed the internalization of CR by the cells guided by the NPs. Cells treated with CR@CarrNPs exhibited higher activity of alkaline phosphatase and higher expression of the main osteogenic genes (Sp7, Col1 and Runx2), and mineralized the extracellular matrix in a higher extent compared to the cells cultivated in absence of the NPs. We posited that these effects were related to the NP-driven internalization of CR by osteoblasts. Our study sheds light on the possible use of CR@CarrNPs as efficient and safe therapeutic tools for the treatment of bone-related diseases.The use of Curcumin (CR) as a bioactive molecule to prevent and treat inflammation- related diseases is widespread. However, the high hydrophobicity hinders the in vivo bioavailability of CR, reducing its therapeutic index. In the present study, we described the use of nanoparticles (NPs) made of kappa-carrageenan (κ-Carr), a sulphated polysaccharide, as cost-effective, biodegradable and biocompatible CR carriers. CR-loaded κ-Carr nanoparticles (CR@Carr NPs) were prepared by mixing a κ-Carr aqueous solution with a CR ethanolic solution. The final suspension was centrifuged and re-suspended in phosphate buffer solution. The NPs' size was tuned by changing the concentration of the polysaccharide. CR@CarrNPs displayed high CR incorporation efficiency (~80 wt%) and a double-exponential curve of CR release at physiological conditions (37 °C and pH 7.4) with a cumulative drug release of 32 wt% after 24 h for the smaller NP. Our results also showed that CR@CarrNPs were not cytotoxic to osteoblasts at concentrations up to 1 μM. Confocal microscopy images revealed the internalization of CR by the cells guided by the NPs. Cells treated with CR@CarrNPs exhibited higher activity of alkaline phosphatase and higher expression of the main osteogenic genes (Sp7, Col1 and Runx2), and mineralized the extracellular matrix in a higher extent compared to the cells cultivated in absence of the NPs. We posited that these effects were related to the NP-driven internalization of CR by osteoblasts. Our study sheds light on the possible use of CR@CarrNPs as efficient and safe therapeutic tools for the treatment of bone-related diseases.